Pengaruh Gender Pada Kinerja UMKM: Sebuah Literatur Review - Sari, Dewi Wulan; Pratikto, Heri; Sopiah, Sopiah (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
The role of women in improving the economy has often been echoed in relation to their work in doing business independently. However, so far, micro, small and medium enterprises managed by women have not been properly developed so that they are able to grow and develop and have optimal competitiveness. Is it true that businesses run by women are less profitable than businesses run by men? This study uses a systematic literature review method by analyzing the results of research in various places related to this, including factors that can be observed so that businesses managed by women can show maximum performance. The results of this study are expected to provide information related to improving performance, especially for women.